2004
DOI: 10.1016/j.molcel.2004.10.028
|View full text |Cite
|
Sign up to set email alerts
|

The First α Helix of Bax Plays a Necessary Role in Its Ligand-Induced Activation by the BH3-Only Proteins Bid and PUMA

Abstract: The mechanism by which some BH3-only proteins of the Bcl-2 family directly activate the "multidomain" proapoptotic member Bax is poorly characterized. We report that the first alpha helix (Halpha1) of Bax specifically interacts with the BH3 domains of Bid and PUMA but not with that of Bad. Inhibition of this interaction, by a peptide comprising Halpha1 or by a mutation in this helix, prevents ligand-induced activation of Bax by Bid, PUMA, or their BH3 peptides. Halpha1-mutated Bax, which can mediate death indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
260
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(290 citation statements)
references
References 24 publications
19
260
1
1
Order By: Relevance
“…It is interesting that the constrained BH3 peptide was found to interact with a site involving helices a1 and a6, different from the canonical binding groove characterized for pro-survival proteins. This finding supported an earlier observation that the first a-helix of Bax participates in an interaction with the BH3 domains of Bid and Puma (Cartron et al, 2004). Binding of the stapled peptide was reported to open the conformation of Bax, as judged by the exposure of the 6A7 epitope, and oligomerization in a buffer devoid of lipids.…”
Section: S131supporting
confidence: 89%
See 2 more Smart Citations
“…It is interesting that the constrained BH3 peptide was found to interact with a site involving helices a1 and a6, different from the canonical binding groove characterized for pro-survival proteins. This finding supported an earlier observation that the first a-helix of Bax participates in an interaction with the BH3 domains of Bid and Puma (Cartron et al, 2004). Binding of the stapled peptide was reported to open the conformation of Bax, as judged by the exposure of the 6A7 epitope, and oligomerization in a buffer devoid of lipids.…”
Section: S131supporting
confidence: 89%
“…The BH3 domain seems to be entirely responsible for this interaction, and is absolutely required for the killing activity of the BH3-only proteins. In addition, Bim, Bid and Puma were also found to interact with Bax (Marani et al, 2002;Cartron et al, 2004;Willis et al, 2007). Bim, Bad and Bmf are unstructured in the absence of a binding partner, and only their BH3 domain becomes structured upon binding a pro-survival protein (Hinds et al, 2007).…”
Section: The Bh3-only Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently shown that the BH3 only proteins Bid and PUMA interacted with the Ha1 of Bax using a bacterial two hybrid screen. 20 The physical interaction between Bax Ha1 and these BH3 only proteins was confirmed by both structural and functional analyses. During this screening, we found that the mitochondrial protein TOM22 was also capable of interacting with Bax Ha1-RFP but not with RFP or the RFP-Ha9 DS184 Bax chimera (data not shown).…”
Section: Resultsmentioning
confidence: 75%
“…During apoptosis, N-terminal cleavage of Bid by caspase-8 produces p15 tBid, the active form which rapidly targets mitochondria and triggers cytochrome c release [72,73]. One important target of tBid on the mitochondrial outer membrane is Bax, a multi-BH domain pro-apoptotic Bcl-2 protein which interacts with the BH3 domain of tBid [74]. In fact, tBid binding to the first α helix of Bax was shown to be crucial for the pro-apoptotic activity of tBid [74].…”
Section: Cardiolipin: Docking Site For Tbidmentioning
confidence: 99%